Kredit Bermasalah , Perputaran Kas Dan Pengaruhnya Terhadap Likuiditas Perusahaan - Mochtar, Hasyim; Irwan, Muhammad Nur; Gaffar, Annisa Lukman; Rajab, Abdul (P3M STIEM, 2021)
Abstract : This research aims to examine and analyze the effect of (i) non-performing loans on liquidity; and (ii) cash turnover to liquidity. This research belongs to the category of quantitative research, where the location taken in this research was carried out at the STIEM Bongaya Makassar Investment Gallery and used secondary data collection methods obtained from the company’s financial statements with the sample selection technique using purposive sampling technique. The population in this research are all banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period with a total of 81 companies, while the sample taken is 40 data on the quarterly financial statements of state-owned banks for 2016-2020. The results obtained from the research variable data have been tested using the classical assumptions test, including: normality assumption test, autocorrelation test, multicollinearity test, and heteroscedasticity test using multiple linear regression data analysis techniques. The results of the research that has been done show that partially non performing loans have a positive and significant effect on liquidity. On the other hand, cash turnover doesn’t have a significant effect on liquidity.